THE EFFECT OF BRAND CREDIBILITY AND SECURITY ON PURCHASE INTENTION IN THE BUKALAPAK MARKETPLACE IN SURABAYA CITY - Ismail, Rizky Riza; Wardhani, Nuruni Ika Kusuma (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
The development of technology and the internet will certainly bring a lot of convenience. Intense competition in the marketplace industry does have a positive impact on consumers, but also has a negative impact on some marketplaces. This study aims to test and find out how much influence brand credibility and security have on buying interest in the Bukalapak marketplace. This study uses primary data obtained from respondents' questionnaire answers. The population of this study were people in Central Surabaya City. The sample used was 130 respondents who had made purchases on the Bukalapak marketplace with purposive sampling technique. The results showed that Brand Credibility and Security had a significant positive effect on Buying Interest in the Bukalapak marketplace in Surabaya City.